The Unwritten Endings: A Deep Dive into the Story Completion Method in Management Research - Berivan Tatar (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Story completion is a novel and intriguing methodological approach that generates a wealth of insightful and broader knowledge about individuals’ perceptions and understanding for researchers across disciplines. However, this method remains underexplored within the management research. To address this gap, this article focuses on the conceptual and methodological origins of the story completion method and provides a synthesis of story completion research in management literature. Our review of findings from seven studies shows that story completion-based research has focused on understanding the perception of menopausal women at work, teachers' teaching approach, and family life during the COVID-19 pandemic within the context of healthcare professionals, social workers, and teachers. Besides, these studies also concentrated on sensitive work-related research topics (discriminatory abuse, gender stereotypes etc.). The sample size and cnumber of stories ranged from 21 to 62 participants. Considering story design, 86% of studies used third-person perspectives. Also, these studies used a comparative design based on gender (male and female manager), personal characteristics (race, mental health etc.), socioeconomic status (low and middle), and different aspects of family life (household tasks, childcare, working from home, etc.). As an analysis method, 43% of studies used reflexive thematic analysis as a data analysis method. Finally, story completion was used as the sole method in the story completion research in management literature.